Impaired acuity of the approximate number system in 22q11.2 microdeletion syndrome - Oliveira, Lívia; Santos, Amanda [UNESP]; Vianna, Gabrielle; Di Ninno, Camila; Giacheti, Célia Maria [UNESP]; Carvalho, Maria; Wood, Guilherme; Pinheiro Chagas, Pedro; Haase, Vitor (American Psychological Association (APA), 2014)
A magnitude comparison deficit has been frequently observed in velocardiofacial syndrome (Del22q11.2). We hypothesized that this deficit extends to impairments in the acuity of the approximate number system (ANS). Three groups of children aged 8-14 years were investigated: Del22q11.2 children (n = 12), low cognitive ability children (LCA; n = 12), and matched typicallydeveloping children (TD; n = 28). All children were assessed with a simple reaction time task and symbolic and nonsymbolic number comparison tasks. To estimate the acuity of the ANS, the Weber fraction (w) was calculated from the nonsymbolic comparison task. The Del22q11.2 group exhibited a significantly higher w compared with the other groups. Importantly, no significant differences were found in w between the TD and LCA groups. The performance pattern of the Del22q11.2 group was similar to the TD group in the symbolic comparison task, and both of these groups had better performance than the LCA group. The impairment of ANS acuity observed in individuals with Del22q11.2 cannot be explained by deficits in general processing speed because no significant group differences were found in the simple reaction time task. These results suggest that lower acuity of the ANS should be added to the behavioral phenotype of Del22q11.2. The absence of impaired ANS acuity in the LCA group is consistent with the hypothesis that number sense is a relatively specific and autonomous domain. Investigations of low ANS acuity in mathematics learning difficulties and Del22q11.2 should be intensified.
Keywords: síndrome del22q11.2; fenótipo; aprendizagem